2003
DOI: 10.1097/01.ccm.0000069731.18472.61
|View full text |Cite
|
Sign up to set email alerts
|

Induced hypothermia in critical care medicine: A review

Abstract: Induced hypothermia has a role in selected patients in the intensive care unit. Critical care physicians should be familiar with the physiologic effects, current indications, techniques, and complications of induced hyperthermia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
187
1
17

Year Published

2005
2005
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 299 publications
(208 citation statements)
references
References 136 publications
3
187
1
17
Order By: Relevance
“…[1][2][3]10 Basic research to elucidate the mechanism of hypothermic treatment has also been performed. Hypothermia has been shown to inhibit the elevation of excitatory amino acid concentration in the brain after ischemia, 11 neuronal apoptosis after spinal cord injuries in rabbits 12 and post-traumatic inflammatory cascades such as IL-1b, iNOS and superoxide in the brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3]10 Basic research to elucidate the mechanism of hypothermic treatment has also been performed. Hypothermia has been shown to inhibit the elevation of excitatory amino acid concentration in the brain after ischemia, 11 neuronal apoptosis after spinal cord injuries in rabbits 12 and post-traumatic inflammatory cascades such as IL-1b, iNOS and superoxide in the brain.…”
Section: Discussionmentioning
confidence: 99%
“…This therapy, which has been applied to cerebral hemorrhage and other brain damages, reduces neuronal degeneration. 1,2 Hayashi et al 3 reported that hypothermic treatment enabled patients, who otherwise would have become brain dead, to reintegrate into the society.…”
Section: Introductionmentioning
confidence: 99%
“…A reduction in temperature slows down the metabolism, including the cerebral metabolic rate, and reduces energy demand 173 : For every 1º C drop in temperature, more than a 5% drop in metabolism has been reported 174,175 . While intra-ischaemic hypothermia reduces energy failure during the insult, the effect of therapeutic hypothermia is to inhibit many of the pathways involved in delayed energy failure and cell death occurring hours after hypoxia and reoxygenation 155,173,176,177 .…”
Section: Mechanisms Of Hypothermic Protectionmentioning
confidence: 99%
“…The rewarming phase of therapy is critical due to the risk of mitochondrial injury, vascular dysregulation, and rebound increases in ICP (Jiang, Yu, & Zhu 2000;Jiang & Yang 2007;Povlishock & Wei 2009). Although the optimum rewarming rate has yet to be determined, most authors advocate rates of approximately 0.5-1 o /hour (Bernard & Buist 2003;Bernard et al 2002;Alzaga, Cerdan, & Varon 2006). At our institution, cooling is generally performed for a minimum of 48 hours.…”
Section: Cerebral Edema Intracranial Hypertension and Cerebral Perfumentioning
confidence: 99%
“…Unfortunately, no comparative trials are available. Induced hypothermia has been investigated as a neuroprotective strategy in many disease states, and is currently the standard of care for comatose patients following cardiac arrest (Bernard & Buist 2003; Mild therapeutic hypothermia to improve the neurologic outcome after cardiac arrest 2002; Bernard et al 2002). Moderate hypothermia has been shown to decrease the cerebral metabolic rate considerably (Rosomoff & Holaday 1954).…”
Section: Cerebral Edema Intracranial Hypertension and Cerebral Perfumentioning
confidence: 99%